Association between the absence of colostrum feeding and symptoms of intestinal obstruction or neonatal necrotizing enterocolitis - Hananto Wiryo; M. Hakimi; A. Samik Wahab; Pitono Soeparto (Indonesian Pediatric Society Publishing House, 2016)
Objective To assess the relationship between withholding colos- trum and symptoms of intestinal obstruction (SIO) or neonatal ne- crotizing enterocolitis (NNEC). Methods This was a longitudinal cohort study in four subdistricts in West Lombok involving mothers and live newborns. Mothers were interviewed about prenatal care, delivery process, and prac- tice of colostrum feedings. Neonates were followed everyday for 28 days by field assistants for signs of intestinal obstruction or NNEC. We used X 2 test to analyze the association between the absence of colostrum feeding and the occurence of SIO and stu- dent t test to compare the average of colostrum feeding between the SIO and the non-SIO group. Results 3420 live newborns between 1993-1994 were observed. 1900 mothers gave colostrum while 1520 did not. The incidence of SIO was 1.8%. There was a significant association between the absence of colostrum feeding and the occurence of the SIO (RR 1.816; 95%CI 1.08-3.06; p=0.028). No infants with NNEC were given colostrum. Conclusion The absence of colostrum feeding is an important risk factor for the occurence of SIO and NNEC in neonates